User Interface Evaluation of the Sumber Alam Ekspres Application Using the Heuristic Evaluation Method - Frobenius, Arvin Claudy; Kurniawan, Rizki Candra (Journal of Applied Informatics and Computing, 2025)
The Sumber Alam Ekspres mobile application is designed to facilitate users in booking bus tickets. Since its launch in December 2020, the app has garnered over 35,000 downloads, averaging 48 downloads per day. Currently, it holds a rating of 4.1 out of 5 on the Google Play Store. User reviews—207 in total—reveal various complaints, particularly regarding mismatched information, malfunctioning features, and unintuitive interface design. To investigate these issues, a usability evaluation was conducted using the Heuristic Evaluation Method with 20 respondents representing different user types and statuses. The evaluation revealed that only one usability principle—Visibility of System Status—achieved a high score (69%). Six heuristics received moderate ratings: Match Between System and the Real World (62.5%), User Control and Freedom (56.5%), Consistency and Standards (53.5%), Error Prevention (52.5%), Recognition Rather Than Recall (59.5%), and Aesthetic and Minimalist Design (63.5%). Meanwhile, three heuristics were rated low: Flexibility and Efficiency of Use (42%), Help Users Recognize, Diagnose, and Recover from Errors (37%), and Help and Documentation (38%). These findings highlight specific areas for improvement in the user interface, particularly in providing adequate guidance, improving efficiency, and ensuring a more intuitive user experience.